Penelitian dalam Bidang Kedokteran Jiwa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
The paper describes various methods of problem-solving during the history of mankind and puts special emphasis on discovering and identification of psychiatric problems. Research methodology in general is explained. Then it reviewed similarities between psychiatric research -- and the general, methodology. Finally, the particularities of psychiatric research are discussed.